The Effect of Work Environment and Career Development on Employee Job Satisfaction at PT. Sinar Musi Jaya Palembang - Utami, Novi; Effendi, RY.; Aryanti, Rahmi; Hermanto, Hermanto (Universitas Dehasen Bengkulu, 2025)
The purpose of this study was to determine how employee job satisfaction at PT. Sinar Musi Jaya Palembang is influenced by career development and the work environment. This study used a descriptive quantitative approach for all 65 employees. After questionnaires were collected, multiple linear regression was used to analyze the data. The results showed that, both partially and simultaneously, the work environment and career development programs increase employee job satisfaction. A comfortable, safe, and supportive work environment has been shown to increase employee job satisfaction. Furthermore, a clear, organized, and sustainable career development program also increases employee motivation and loyalty. Therefore, companies must continue to create a pleasant workplace and offer real career opportunities for their employees. This is crucial for increasing job satisfaction, which can positively impact company performance and productivity.